Effects of self-instructional training on second- and third-grade hyperactive children: a failure to replicate. - Friedling, C (1979)
Bornstein and Quevillon (1976) demonstrated generalization from a 2-hour self-instructional training session to on-task behavior in the classroom with 4-year-old overactive children. In an attempt to replicate this work with older children, eight 7- and 8-year-old hyperactive children were assigned to either a self-instructional training group or an attention-practice control group. On-task behavior in the classroom and performance measures in reading and arithmetic were assessed. The level of difficulty of these tasks was varied. The results of Bornstein and Quevillon's (1976) study were not replicated, although the subsequent introduction of a token program significantly increased on-task behavior.